After stroke bidirectional modulation of soleus stretch reflex amplitude emerges during rhythmic arm cycling - Mezzarane, Rinaldo A.; Nakajima, Tsuyoshi; Zehr, E Paul (Frontiers in Human Neuroscience, 2014)
Objectives: After stroke a typical presentation is exaggerated stretch reflexes (SR) on the more affected (MA) side. The present study evaluated the contribution of presynaptic inhibition (PSI) induced by arm cycling and homosynaptic depression (HD) to the modulation of hyperreflexia at the ankle after stroke. Possible asymmetry of these effects between the MA and less affected (LA) legs was also assessed. Methods: Soleus SR was conditioned by: arm cycling at 1Hz (to increase Ia PSI); or, a preceding conditioning tendon tap applied 1 s before the test stimulus (to induce HD). The extent of conditioning effects was compared between the MA and the LA legs. Results: For both MA and LA legs, rhythmic arm movement induced a bidirectional effect in different participants, either increasing or decreasing SR amplitude (p< 0.05). HD had a significant effect in both legs (p< 0.05), however, the effect of both a previous muscle stretch and arm cycling was not different between the MA and the LA legs. Conclusion: Our data reveal a bidirectional reflex modulation induced by arm cycling that produced facilitation in some and suppression in other participants after stroke. Relative SR amplitude modulation did not differ between the LA and MA legs. We speculate that alterations in SR amplitude modulation after stroke may reflect specific changes in both presynaptic afferent transmission mechanisms and fusimotor control. Significance: The present findings open new perspectives on the characterization of pathophysiology of stroke during the performance of functionally relevant motor tasks.